High-performance liquid chromatography and chemometric techniques for analytical method development (2018)
As it is worldwide known, high-performance liquid chromatography (HPLC) is a highly useful technique employed for the separation, detection and determination of a number of compounds contained in an analyzed matrix. Undoubtedly, the use of HPLC offers a wide range of advantages in the identification and quantification of samples polluted with substances present at ultra-trace levels, in the range of μg/L or ng/L, such as the monitoring of international regulation accomplishment in terms of water quality. However, in order to take a maximum profit of these advantages, chromatographic operating conditions and sample preparation procedures, if required, must be optimized. For this purpose, chemometric techniques, including design of experiments and principal component analysis, among other multivariate data analysis instruments, offer a powerful tool in contrast to the utilization of one-variable-at-a-time procedures. This work presents the importance of using HPLC in analytical chemistry, as well as the positive aspects related to the use of chemometric approaches for the optimization of processes during the development of analytical methods. Finally, case studies about real applications of chemometric tools focusing on the analysis of water samples polluted with a mixture of polycyclic aromatic hydrocarbons are presented. © 2018 Nova Science Publishers, Inc. © 2018 by Nova Science Publishers, Inc. All rights reserved.